Engineering Division Website Goods Control System Based Using the Laravel 9 Framework: Case Study of a Pharmaceutical Company in Bandung - Handiyana, Haris; Apriantsani, Dheni; Suherman, Asep; Sudarsono, Nono (Electronic, Business, Management and Technology Journal, 2023)
Technology is becoming progressively sophisticated and expediting all processes and facets across several domains, mainly using precise technology. Within a company, digitalization is crucial in facilitating many processes like recapping and reporting. Digitalization refers to the transformation of physical commodities into a digital format. On the other hand, semi-computerization has yet to fully optimize the current computerized system fully, making it inefficient and time-consuming. There is a significant demand for generating data reports on borrowed and returned things. However, there are frequent challenges in accurately determining the availability of these products, as the process is currently done manually using a web-based application. The research methodologies include survey, Research & Development, and Field Study. The RUP (Rational Unified Process) system development process utilizes UML (Unified et al.) modeling techniques, including Use Cases, Use Case Scenarios, Activity Diagrams, Sequence Diagrams, and Class Diagrams. The findings derived from this conclusive project application and report are as follows: The synchronization of data between physical and reporting may be easily managed due to the inclusion of a printing feature in this application tailored to the specific needs of borrowers and returners.